Structural changes and thermal stability of charged LiNixMnyCozO₂ cathode materials studied by combined in situ time-resolved XRD and mass spectroscopy - Bak, Seong-Min; Hu, Enyuan; Zhou, Yongning; Yu, Xiqian; Senanayake, Sanjaya D; Cho, Sung-Jin; Kim, Kwang-Bum; Chung, Kyung Yoon; Yang, Xiao-Qing; Nam, Kyung-Wan (ACS applied materials & interfaces, 2014)
Thermal stability of charged LiNixMnyCozO2 (NMC, with x + y + z = 1, x:y:z = 4:3:3 (NMC433), 5:3:2 (NMC532), 6:2:2 (NMC622), and 8:1:1 (NMC811)) cathode materials is systematically studied using combined in situ time-resolved X-ray diffraction and mass spectroscopy (TR-XRD/MS) techniques upon heating up to 600 °C. The TR-XRD/MS results indicate that the content of Ni, Co, and Mn significantly affects both the structural changes and the oxygen release features during heating: the more Ni and less Co and Mn, the lower the onset temperature of the phase transition (i.e., thermal decomposition) and the larger amount of oxygen release. Interestingly, the NMC532 seems to be the optimized composition to maintain a reasonably good thermal stability, comparable to the low-nickel-content materials (e.g., NMC333 and NMC433), while having a high capacity close to the high-nickel-content materials (e.g., NMC811 and NMC622). The origin of the thermal decomposition of NMC cathode materials was elucidated by the changes in the oxidation states of each transition metal (TM) cations (i.e., Ni, Co, and Mn) and their site preferences during thermal decomposition. It is revealed that Mn ions mainly occupy the 3a octahedral sites of a layered structure (R3̅m) but Co ions prefer to migrate to the 8a tetrahedral sites of a spinel structure (Fd3̅m) during the thermal decomposition. Such element-dependent cation migration plays a very important role in the thermal stability of NMC cathode materials. The reasonably good thermal stability and high capacity characteristics of the NMC532 composition is originated from the well-balanced ratio of nickel content to manganese and cobalt contents. This systematic study provides insight into the rational design of NMC-based cathode materials with a desired balance between thermal stability and high energy density.